2021
DOI: 10.3390/agronomy11091699
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis Reveals That Lenticel Damage Does Not Result in Black Spot Development but Enhances Dehydration in Persea americana Mill. cv. Hass during Prolonged Storage

Abstract: Black spot corresponds to a physiological disorder of the type of oxidative stress that occurs after the prolonged postharvest storage of Persea americana Mill. cv. Hass fruit. Industry tends to confuse this disorder with pathogen attack (Colletotrichum gloeosporioides), chilling injury, mechanical damage during harvest and transport or lenticel damage. The main objectives of this research were: (i) to develop a method to assess and differentiate lenticel damage and black spot and (ii) to study the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Pre-harvest factors such as maximum temperatures and relative humidity during growth and development have also been reported to be negatively associated with black spot development [5]. Similarly, Lindh et al [6] reported that lenticel damage does not result in black spots, and the harvest system did not correlate to the incidence of black spots. Controlled atmosphere (CA) has also been studied showing a significant reduction in black spot incidence, even though this disorder is orchard dependent [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-harvest factors such as maximum temperatures and relative humidity during growth and development have also been reported to be negatively associated with black spot development [5]. Similarly, Lindh et al [6] reported that lenticel damage does not result in black spots, and the harvest system did not correlate to the incidence of black spots. Controlled atmosphere (CA) has also been studied showing a significant reduction in black spot incidence, even though this disorder is orchard dependent [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit were evaluated for russet, dry matter, skin wound, lenticel damage, weight loss, external browning, blackspot incidence, anthracnose, fruit vascular and pulp damage, and firmness following previous fully described methodologies after harvest and at cold chamber exit and at ready‐to‐eat stage (RTE; 4–8 N firmness) (Uarrota et al ., 2020; Lindh et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The aetiology of blackspot physiological disorder is not fully understood and is matter of interest for Chilean avocado industry. Lindh et al ., 2021 recently developed an image analysis‐based method to analyse and identify lenticel damage and blackspots but found no correlation between the two. Uarrota et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The market for avocado processing has increased significantly in recent years and its value is expected to continue to increase beyond 2024 with new products entering the market such as guacamole, frozen slices, sauces, purees, canned avocados, dried avocados, and avocado oil [2]. Increasing evidence of the health benefits of avocado is leading to increased consumption and stimulating research [3,4,5,6], not only on the potential health benefits, but also on all other factors that may influence the external quality of the product in the final market. To extend the shelf life of fresh fruit after harvest, cold storage is the first issue, whether in combination with controlled atmosphere or not.…”
Section: Introductionmentioning
confidence: 99%